Comparison of the Effectiveness of Ductus Arteriosus Stenting and Systemic-to-Pulmonary Artery Shunt Placement in a Cohort of Newborns with Duct-Dependent Pulmonary Circulation - Anzhelika O. Mykhailovska; Oleksandra O. Motrechko; Andrii K. Kurkevych; Andrii V. Maksymenko (Ukrainian Journal of Cardiovascular Surgery, 2024)
In newborns with congenital heart defects and duct-dependent pulmonary circulation, the first stage of palliative intervention may involve the systemic-to-pulmonary artery shunt (SPAS) placement or the patent ductus arteriosus (PDA) stenting. SPAS placement is a traditional method, but the trend towards reducing the invasiveness of surgical interventions has led to PDA stenting use as a preferred method to ensure a reliable source of pulmonary blood flow.The aim. To compare pre- and postoperative indicators, complications, and long-term outcomes in two groups of patients after SPAS placement and PDA stenting.Materials and methods. This single-center retrospective study included 82 newborns who underwent SPAS placement (Group I) and 47 patients who underwent PDA stenting (Group II) from 2015 to 2023. Baseline clinical data were similar in both groups. The arterial blood oxygen saturation (SaO2) was significantly lower in the PDA stenting group compared to the SPAS group (65.7 ± 11.1% vs. 79.2 ± 10.6%, respectively) (p < 0.00001). There was higher percentage of genetic/concomitant pathology in Group II, 13 (27.6%) versus 10 (12.2%), p = 0.02.Results. There was no statistically significant difference between the analyzed patient groups in clinical status indicators in the postoperative period, including: the duration of artificial lung ventilation (165.5 ± 94 and 150 ± 113 in groups I and II, respectively) (p = 0.87) and length of stay in the intensive care unit (14 ± 7 and 13.6 ± 9.4 days) (p = 0.76). However, SaO2 was higher in Group I than in Group II (81 ± 5.5% vs. 85 ± 4.6%, respectively) (p = 0.02). Before the next stage of surgical correction, the Nakata index in Group II was significantly higher than that in Group I (225 ± 87.4 mm2/m2 vs. 168 ± 35.9 mm2/m2, respectively) (p = 0.048). The percentage of reoperations was higher in Group II (17 [36.1%] versus 14 [17.1%]), however, the overall (14.9% and 26.8%) and late (9.1% and 19.5%) mortality rates were lower in Group II.Conclusion. Considering the similar results in both patient groups, stenting may be an effective option to increase the pulmonary blood flow in newborns. Due to its minimally invasive procedure, this method may be a choice for premature newborns and children with complex comorbidities. However, SPAS placement remains an important palliative intervention, particularly in cases where ductus arteriosus is tortuous and in congenital heart defects with complex intracardiac anatomy postponing radical correction until older age.